2022
DOI: 10.1001/jamasurg.2022.1362
|View full text |Cite
|
Sign up to set email alerts
|

Association of Matrix Metalloproteinase 7 Expression With Pathologic Response After Neoadjuvant Treatment in Patients With Resected Pancreatic Ductal Adenocarcinoma

Abstract: IMPORTANCEThe use of neoadjuvant therapy (NAT) in resectable pancreatic ductal adenocarcinoma (PDAC) remains controversial. A favorable pathologic response (complete or marked tumor regression) to NAT is associated with better outcomes in patients with resected PDAC. The role of NAT for early systemic control compared with immediate surgical resection for PDAC is under investigation. In the era of precision medicine, biomarkers for patient selection and prediction of therapy response are crucial.OBJECTIVE To e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
22
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 16 publications
(24 citation statements)
references
References 35 publications
2
22
0
Order By: Relevance
“…In a discovery cohort of 23 patients, the study found that that lower expression of matrix metalloproteinase 7 ( MMP7 ) was associated with more favorable pathologic response, which is a strong surrogate for outcomes of PDAC patients. 15 The finding was confirmed in a validation cohort of 80 patients: patients with negative MMP7 immunohistochemistry staining were significantly more likely to have a more favorable pathologic response to NAT (odds ratio 21.25, 95% CI 6.19–72.95, p = 0.001). These results show great promise for use of RNA sequencing and proteomic analysis to identify targets that can predict NAT response.…”
Section: Administration Of Nat Based On Biomarkersmentioning
confidence: 70%
See 2 more Smart Citations
“…In a discovery cohort of 23 patients, the study found that that lower expression of matrix metalloproteinase 7 ( MMP7 ) was associated with more favorable pathologic response, which is a strong surrogate for outcomes of PDAC patients. 15 The finding was confirmed in a validation cohort of 80 patients: patients with negative MMP7 immunohistochemistry staining were significantly more likely to have a more favorable pathologic response to NAT (odds ratio 21.25, 95% CI 6.19–72.95, p = 0.001). These results show great promise for use of RNA sequencing and proteomic analysis to identify targets that can predict NAT response.…”
Section: Administration Of Nat Based On Biomarkersmentioning
confidence: 70%
“…More recently, Shoucair et al. 15 used targeted RNA sequencing of frozen FNA biopsy specimens to identify genes with atypical expression that were associated with patient response to NAT. In a discovery cohort of 23 patients, the study found that that lower expression of matrix metalloproteinase 7 ( MMP7 ) was associated with more favorable pathologic response, which is a strong surrogate for outcomes of PDAC patients.…”
Section: Administration Of Nat Based On Biomarkersmentioning
confidence: 99%
See 1 more Smart Citation
“…Using the current tumor regression grading system according to the College of American Pathologists (CAP), favorable PR was defined as a CAP score of 0 or 1, and unfavorable PR as a CAP score of 2 or 3. 2 In the analyzed cohort of patients who underwent NAT and resection for PDAC (n = 334) (Figure 1A and Table S1), OSA was significantly associated with male sex, resectable disease stage at diagnosis, shorter duration of NAT, increased tumor size, lymphovascular and perineural invasion, R1 margin, and unfavorable PR to NAT. In addition, OSA was an independent predictor of unfavorable PR in this study.…”
Section: E T T E R T O T H E E D I T O R Obstructive Sleep Apnea Pred...mentioning
confidence: 97%
“…A growing body of evidence suggests that neoadjuvant therapy (NAT) improves surgery candidacy as well as postoperative outcomes in these patients, particularly in patients with a favorable pathologic response (PR). 2 There is, however, a lack of predictors of response to therapy before surgical resection.…”
Section: E T T E R T O T H E E D I T O R Obstructive Sleep Apnea Pred...mentioning
confidence: 99%